STUDI TENTANG INTERAKSI SOSIAL ANTARA PESERTA DIDIK DI SDK SANTA MARIA ASSUMPTA KOTA KUPANG - Dau, Yoseph Lodowik Deki; Bria, Florens Maxi Un (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2023)
This research was carried out with the aim of examining the social interactions of students at SDK Santa Maria Assumpta, Kupang City. The results of the research show that the collaboration aspect obtained an indicator achievement of 71.11%, the communication aspect obtained an indicator achievement of 78.52%, the empathy aspect obtained an indicator achievement of 58.67%, the problem solving aspect obtained an indicator achievement of 68.52%, and the respect for diversity aspect achieved an indicator achievement of 85.56%. The positive impact of social interaction between students at SDK Maria Assumpta Kupang City is the creation of relationships and relations between students, students can improve their ability to communicate with other people, students are able to manage their emotions when facing challenges or problems in relationships with friends, teachers and school staff, students can transfer positive habits in their social interactions at school to their family life. Meanwhile, negative impacts include misunderstanding and bullying, dominating behavior towards other students who are in lower positions, as well as social restrictions which cause feelings of exclusion and social isolation for affected students. Efforts are made to create social interaction for students at SDK Santa Maria Assumpta, Kupang City, namely that the school needs to pay attention to the importance of aspects of students' social life so that students can develop as good and healthy individuals in carrying out social interactions in the school environment, in within the family and in the community. Apart from that, homeroom teachers need to translate school policies through educational activities that can increase social interaction between students at SDK Maria Assumpta, Kupang City.